A qualitative exploration of women’s expectations of birth and knowledge of birth interventions following antenatal education - Anna Davies; Michael Larkin; Lucy Willis; Narendra Mampitiya; Mary Lynch; Miriam Toolan; Abigail Fraser; Kate Rawling; Rachel Plachcinski; Sonia Barnfield; Margaret Smith; Christy Burden; et al. (BMC Pregnancy and Childbirth)
Abstract Background Expectations of birth, and whether they are met, influence postnatal psychological wellbeing. Intrapartum interventions, for example induction of labour, are increasing due to a changing pregnant population and evolving evidence, which may contribute to a mismatch between expectations and birth experience. NICE recommends antenatal education (ANE) to prepare women for labour and birth, but there is no mandated UK National Health Service (NHS) ANE curriculum. We aimed to explore women’s expectations of childbirth and their understanding of common interventions and complications following NHS and non-NHS ANE. Method Qualitative focus groups were conducted with postnatal women (< 12 months postpartum) aged ≥ 16, who had received antenatal care at a single NHS Trust. A semi-structured topic guide was used to explore birth expectations following attendance at ANE and knowledge of birth interventions and complications. Data were transcribed and thematic analysis was undertaken by at least two researchers. Results 46 women (mean age: 33.5years; 81% white British) participated across eight groups. 65% were primiparous, 35% had a caesarean birth. 50% attended NHS ANE and 59% non-NHS ANE. Participants perceived that a ‘hierarchy of birth’ was presented within ANE classes, where a ‘better birth’ involved vaginal birth, minimal pain relief and limited intervention. Participants described expectations of control and choice over their birth, though some described being encouraged to be open-minded about the course it may take. Participants identified a mismatch between their expectations and subsequent experiences, which adversely impacted their psychological wellbeing. While participants received information about common birth interventions and complications, limited time spent on these during classes resulted in expectations that they were rare. Participants felt that receiving sensitively presented information about the frequency of interventions could prepare women and support their psychological wellbeing after birth. Conclusions Women’s expectations of birth are informed by ANE which may precipitate a mismatch between expectations and experience. Better information about risk factors and frequency of labour and birth interventions may support women to develop evidence-informed expectations of birth, reducing the expectation-experience gap, with consequent impact on maternal postnatal wellbeing. A mandatory minimum curriculum for ANE is needed to ensure high-quality education is available to all.